The Relationship Between Intercultural Sensitivity, World Music Preferences and Preferences for Visual Artwork from Other Cultures - Dobrota, Snježana; Krnić, Marijo; Brajčić, Marija (Revija za elementarno izobraževanje, 2022)
The results do not confirm the influence of the type of secondary education completed on intercultural sensitivity, world music preferences or on preferences for visual artwork from different cultures. Neither was the influence of participants’ year of study on their level of intercultural sensitivity confirmed, but we did confirm that older students show greater preferences for world music and visual artwork from different cultures when compared to younger students. Furthermore, the study confirmed a connection between intercultural sensitivity, on the one hand, and preferences for world music and visual artwork from different cultures, on the other.
Keywords: intercultural sensitivity, preference for world music, preference for artwork from different cultures, teaching music, teaching visual arts and fine arts